Effects of selected therapeutic aerobic exercise on remedial case of premenstrual syndrome in case of Arba Minch University - K. Abebe; M. Deyuo; W. Aychiluhim (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: The purpose of this study was to assess the effect of selected therapeutic 12 weeks regular aerobic exercise on remedial case of premenstrual syndrome students. Materials: A quasi-experimental study was used on a randomly selected 30 female students aged 18 to 30 years who meet the eligibility criteria at Arba Minch University. Participants were divided in to two groups: experimental group (n=15) and control group (n=15) for comparison purpose. The therapeutic aerobic exercise duration was 40-60 minutes and carried out for 12 weeks with three sessions per week. In this study the premenstrual symptoms questionnaire consists of 8 domains of used. The domains were pain, concentration, behavioral change, autonomic reactions, water retention, negative effect, arousal and control. A paired t-test statistical method was used for data analysis. SPSS version 20 was used for data management and analysis. Result: The study found mean scores of negative reaction decreased after 12 weeks with a frequency of 3 per week therapeutic aerobic training in the experimental group but not in the control. Further, a statistically significant change was observed for all measured variables for experimental group. However, there was no a statistically significant change for the controls. The selected therapeutic aerobic exercise training program on treating premenstrual syndrome had a significance effects on experimental group and students who practiced for twelve weeks with a repetition of three times per week. Conclusion: Twelve weeks of regular therapeutic aerobic exercise with three sessions per a week with intensity of 40 to 60 minutes reduces the severity of feeling premenstrual syndrome symptoms (PMS).